Total synthesis of racemosol and de-O-methylracemosol, potent cyclooxygenase (COX) inhibitors and antimalarial agents - Patcharaporn Sae-Lao (2018)
The total synthesis of antimalarial and cyclooxygenase inhibitors, racemosol and de-O-methylracemosol, is described. The key steps involved the lateral lithiation reaction of ortho-methyl tolulate and the pyran formation via a tandem demethylation-cyclization reaction. © 2005 Elsevier Ltd. All rights reserved.